Economics in Ireland - Frances Ruane; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
The measurement of academic output in Ireland is of growing interest in the context of the government's strategy to identify and support centres of research excellence and to encourage inter-institutional collaboration in both research and fourth- level education. This paper looks at research output within the economics profession in these various centres, building on an earlier literature (Barrett and Lucey, 2003: Coupe and Walsh, 2003) which looked at the research output of Irish economists in peer-reviewed journals. Using a relatively new data-base, Scopus, we find that research output in the Republic of Ireland is heavily skewed by researcher and by institution and that the more productive and most cited Irish research economists are heavily concentrated in the Greater Dublin area.
Keywords: 330; Wissenschaftliches Arbeiten; Ökonomen; Standortfaktor; Irland